Modeling the Digital Al-Quran User Experience as Tahfidzul Quran Media using the Task-Centered System Design - Adinda Rahma Khumairah; Mira Kania Sabariah; Veronikha Effendy (JURIKOM (Jurnal Riset Komputer), 2022)
The development of technology in the world from time to time continues to progress so rapidly that various kinds of tools in the world are now converted into digital tools that facilitate the activities of human life. However, with the development of this technology, unfortunately, it has not had much impact in the realm of Tahfidz Al-Quran. Media Tahfidz Al-Quran, currently available in the community, is to follow a program that learns under the guidance of a teacher or study together in one place. Based on a survey conducted by interviews using several digital Al-Quran applications available in the android play store as a media for Tahfidz Al-Quran. The usability aspect that has not been fulfilled in using digital Al-Quran as a media for Tahfidzul Quran is efficiency and satisfaction. Therefore, to properly use Tahfidz al-Quran in digital form, it is required to have the appropriate UX modeling in line with the needs of Tahfidz Al-Quran. Because Task-Centered System Design (TCSD) method puts a strong emphasis on user demands and task requirements, this study intends to create a design using TCSD.Furthermore, to ensure that the model developed is within the circumstances and user characteristics, the product model outcomes will be assessed using the System Usability Scale (SUS). The findings of this study provide recommendations for the Tahfidz Al-Quran application's user interface design and have an improved usability score at 88.75, which is expected to be a benchmark for the Tahfidz Al-Quran application. Therefore, the TCSD method can also raise the SUS usability value in the application